EVALUASI KOMPETENSI LITERASI INFORMASI SISWA MENGGUNAKAN MODEL MIL CONCEPT AND APPLICATION SCHEME DI SMP NEGERI 29 PADANG - Haris Septiansah; Yona Primadesi (CV. ADIBA AISHA AMIRA, 2023)
This study aims to describe the level of information literacy competency of students using the MIL Concept and Application Model scheme at SMP Negeri 29 Padang. This study uses quantitative research with descriptive methods. The population of this study was students of SMP Negeri 29 Padang with a total of 288 students, while the sample used the proportion formula, namely 72 students. The instrument used in this research is test questions. To analyze the data in this study using descriptive analysis with the frequency formula. The results showed that the level of information literacy competency of students based on indicators of formulating information needs earned an average score of 80.5. The indicator of using and accessing information gets an average score of 60.6. The indicator of using information ethically gets an average score of 77.7. The indicator of using ICT (technology, information, and communication get an average score of 85.4. Overall the level of students' information literacy ability gets an average score of 76 which indicates that the level of information literacy skills of students of SMP Negeri 29 Padang is considered good.